Marsh foraminifera of Prince Edward Island: Their recent distribution and application for former sea level studies - Scott, David; Williamson, Mark; Duffett, Thomas (Atlantic Geology, 1981)
ABSTRACT A detailed survey of all marsh areas of Prince Edward Island, Canada, was undertaken and the Information derived was used to determine four optimal areas (i.e., thickest marsh deposits) for sea level studies. Although extensive studies of marsh foraminifera have been conducted in Nova Scotia, the mixed tidal system in Prince Edward Island necessitated further investigations which suggested different relationships in some foramlniferal distributions, possibly linked to the tidal regime of the Gulf of St. Lawrence. Plant species distributions were markedly different, indicating that plant remains, even if preserved, would not be suitable sea level indicators. Using marsh foramlniferal zonations in subsurface sediments, four sea level curves were determined. These curves encompass the last 3000 years of submergence on Prince Edward Island. Average rates of relative sea level rise in the east (14-19 cm/century) were almost twice that obseived in the west (8 cm/century). This contrasts with previous work that suggested the island had been subsiding at a uniform rate for the last 3000 years. The data obtained here helps to calibrate recently derived geophysical models of the earth's response following deglaciation. Taxonomically, a new genus of marsh foraminifera (PBeudothurarrmina n. gen. Scott, Medioli and Williamson) has been proposed with the type species being Thuranmina (?) limnetis, Scott and Medioli described from marsh sediments in Nova Scotia.